(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: Digital tools are widely utilised to improve communication and information exchange among healthcare professionals. The cantonal hospital in Lucerne was the first to implement the Epic clinical information system in a German-speaking country, including information access for primary care physicians via an electronic health record portal. OBJECTIVES: This study assessed how primary care physicians perceive the communication with hospitals in the canton of Lucerne, including their preferences for discharge summary contents and experiences and utilisation of a regionally implemented electronic health record portal. METHODS: We performed an online survey among primary care physicians and contacted all 323 primary care physicians enlisted as members of the cantonal medical society in Lucerne, Switzerland. RESULTS: A total of 109 primary care physicians completed the online survey (34% response rate). Half of the primary care physicians were satisfied with hospital communication. Three-quarters (n = 83) wanted to be informed of patients’ emergency hospital admission within 48 hours, but only 30% (n = 33) reported being notified. In discharge summaries, primary care physicians expect information on the diagnosis, medication, therapies, and recommendations for follow-up care. A large portion of primary care physicians deemed the electronic health record portal beneficial for patient management. Most primary care physicians utilise the portal to retrieve patient data, but it is rarely used for patient referrals. CONCLUSION: Half of primary care physicians were satisfied with communication with regional hospitals. Primary care physicians reported a lack of timely notifications or reports about emergency admissions, in-hospital deaths, and discharges of their patients. Primary care physicians value the electronic health record portal as a supporting tool for patient management.